The Grimm brothers and the Germanic past - Antonsen, Elmer H.; Marchand, James Woodrow; Zgusta, Ladislav (Amsterdam studies in the theory and history of linguistic science, 2010)
The pioneering work of Jacob Grimm and Wilhelm Grimm in the areas of Germanic comparative and historical linguistics, lexicography, philology, and medieval studies places them squarely among the most important figures in the history of the language sciences. The contributions to this volume present a fascinating and timely reevaluation and reaffirmation of the significance of the Grimm Brothers' work in these areas, all of which the Grimms viewed as necessary components in their search for the essence of the German and Germanic Volksgeist
Includes one contribution in German. - Rev. version of papers from the International Bicentenary Symposium on the Brothers Grimm, held Apr. 10-12, 1986, at the University of Illinois at Urbana-Champaign. - Includes bibliographical references (pages 141-155) and index. - Description based on print version record
Rev. version of papers from the International Bicentenary Symposium on the Brothers Grimm, held Apr. 10-12, 1986, at the University of Illinois at Urbana-Champaign
Includes bibliographical references (pages 141-155) and index
Description based on print version record
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002
Keywords: Grimm, Wilhelm 1786-1859 -- Congresses; Grimm, Jacob 1785-1863 -- Congresses; Grimm, Wilhelm Karl 1786-1859 -- Congrès; Grimm, Jakob Ludwig Karl 1785-1863 -- Congrès -- Grimm, Wilhelm 1786-1859 -- Congresos y asambleas -- Grimm, Jacob 1785-1863 -- Congresos y asambleas -- Grimm, Jacob -- Grimm, Wilhelm -- Geschichte 1812-1862; Grimm, Jacob -- 1785-1863 -- Congresses; Grimm, Wilhelm -- 1786-1859 -- Congresses; Grimm, Wilhelm; Congresos y asambleas; Grimm, Wilhelm; Grimm, Jacob; Grimm, Jacob; Congresos y asambleas; Germany; Electronic books; Konferenzschrift -- 1986 -- Urbana, Ill.; Konferenzschrift